2003
DOI: 10.1007/s00204-003-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

Short period exposure to di-(2-ethylhexyl) phthalate regulates testosterone metabolism in testis of prepubertal rats

Abstract: Exposure of pubertal rats to di-(2-ethylhexyl) phthalate (DEHP) for 14 days was reported to result in reduced testosterone (T) biosynthesis by altering androstenedione 17beta-hydroxysteroid dehydrogenase (17beta-HSD) activity. However, our study indicated that shorter period exposure of DEHP (100 or 1000 mg/kg for 5 days) to 4-week-old male rats did not affect the activity of 17beta-HSD, the rate-limiting enzyme of T biosynthesis in the testis. Testosterone 5alpha-reductase (T5alpha-R) activity in the testis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
6
27
0
Order By: Relevance
“…Previous studies reported that neonatal exposure to DEHP significantly affected testicular growth and development as a result of the reduced testosterone production. 14,20,21) However, the molecular mechanisms of DEHP-induced testic- ular genes associated with steroidogenesis and spermatogenesis expression in rodents are still unclear. This study examined the differentially expressed genes involved in the testicular toxicity caused by long-term exposure to DEHP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that neonatal exposure to DEHP significantly affected testicular growth and development as a result of the reduced testosterone production. 14,20,21) However, the molecular mechanisms of DEHP-induced testic- ular genes associated with steroidogenesis and spermatogenesis expression in rodents are still unclear. This study examined the differentially expressed genes involved in the testicular toxicity caused by long-term exposure to DEHP.…”
Section: Discussionmentioning
confidence: 99%
“…5) Although the mechanism of steroid biosynthesis pathway in the testis is known, recent studies indicate a close link between PPAR and other nuclear receptors in the testes. 14,15) Lovekamp-Swan et al 16) suggested that PPAR ligands suppressed aromatase mRNA levels in the rat ovarian granulose cells but had no effect on P450scc mRNA. It is unclear if this effect was mediated by estrogen receptor (ER).…”
Section: Introductionmentioning
confidence: 99%
“…It also reduces testicular T production in vivo and T levels in the testis [21]. Other studies have reported that exposure of rats to DEHP (200 mg/kg/day) causes various effects, including a 77% decrease in the activity of the steroidogenesis enzyme 17β-hydroxysteroid dehydrogenase, a 50% reduction in T production in Leydig cells [22], enhanced testosterone 5α-reductase (T5α-R) activity in the testis [23], and reduced epididymal sperm density and motility [24].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium levels, protein kinase C (PKC) and mitogen-activated protein kinase (MAPK) activities are involved in the regulation of cPLA 2 activity [2,8,34]. AA, which is generated by cPLA 2 , is metabolized to thromboxane A 2 , 12-hydroxyeicosa-tetraenoic acid (12-HETE) and 20-HETE by cyclooxygenase-2 (COX-2), 12-lipoxygenase (12-LOX) and CYP4A1, respectively [20].We have recently demonstrated that DEHP disrupts the metabolism of testosterone in prepubertal rat testis [24]. There are several factors, such as hormones, zinc concentration, reactive oxygen species and apoptosis, involved in the toxic mechanisms of DEHP-induced testicular atrophy [15, …”
mentioning
confidence: 99%
“…We have recently demonstrated that DEHP disrupts the metabolism of testosterone in prepubertal rat testis [24]. There are several factors, such as hormones, zinc concentration, reactive oxygen species and apoptosis, involved in the toxic mechanisms of DEHP-induced testicular atrophy [15, …”
mentioning
confidence: 99%